النقد الاجتماعي في شعر معروف الرصافي في ضوء القصيدة "الأرملة المرضعة": Social Criticism in the Poetry of Maʿrūf al-Raṣāfī in Light of the Poem “The Nursing Widow” (Khairulummah, 2025)
This study examines the social criticism in the poetry of Ma'ruf al-Rusafi, with particular focus on his poem “الأرملة المرضعة” as a representative model of social poetry in modern Arabic literature. Living through a period of intense political and social transformation in Ottoman and Iraqi society, al-Rasāfī employed poetry as a conscious instrument of reform, directing his verse toward exposing injustice, poverty, ignorance, and moral decline within his community.The paper analyzes how the poem portrays the tragic condition of a poor widow and her infant as a vivid symbol of the suffering of marginalized social groups. Through detailed imagery, emotional expression, and direct moral appeal, the poet transforms an individual human scene into a powerful critique of societal negligence, the absence of compassion, and the failure of the wealthy and influential to uphold social responsibility. The study further highlights the ethical values embedded in the poem, such as sympathy for the weak, relief for the distressed, preservation of human dignity in charity, altruism, and the promotion of mercy and social solidarity.By tracing the linguistic, emotional, and thematic dimensions of the poem, this research demonstrates how al-Rasāfī’s poetry transcends traditional praise and satire to become a vehicle for conscious social reform. The poem emerges not merely as a literary text, but as a moral and social statement that calls for awareness, responsibility, and collective compassion. The study concludes that “الأرملة المرضعة” stands as a significant example of social criticism in modern Arabic poetry and reflects al-Rasāfī’s broader reformist vision of society.